MICROSTRUCTURE EVALUATION OF SERVICE AGED AND REJUVENATED NICKEL SUPER ALLOYS USING HOT ISOSTATIC PRESSING TREATMENT - Biyamin S.A.; Bahari A.M.S.; Peng N.G.; Sanmugham T.; Ghazali R.; Ramli R.; Azmin A.N. (Microscopy Society of Malaysia, 2023)
The design life of gas turbine blades is normally 48,000 equivalent operating hours (EOH) or 72,000 EOH based on the original equipment manufacturer (OEM) recommendation. Extending the service life of gas turbine blades is a huge advantage in the aspect of capital cost-saving in the power plant industries. The coarsening and shape transformation of ?? precipitates are one of the main life-limiting factors for gas turbine blades. Conventional heat treatment could not restore or recover ??-phase precipitates to their original morphology. In this study, hot isostatic pressing (HIP) treatment was used to improve the material properties of the blades to nearly zero-hour operation and prolong the life of gas turbine blades. HIP rejuvenation applies high temperature and pressure to close the micropores, retransform the microphases (i.e., ??-phase precipitates), and heal the material properties. For this case study, three HIP parameters were applied on nickel-based superalloy (GTD-111). Microstructure characterization was carried out on new, aged, and HIP-treated GTD-111 alloys using field emission scanning electron microscopy (FESEM). The microstructure after HIP treatment exhibited significant improvement and recovery in the morphology of ?? precipitates. The hardness of HIPed blade samples appeared consistent at 440 HV and did not deviate significantly from new materials with an average value of 439 HV. The average size of ?? precipitates was successfully reduced from 1.3 m (degraded state) to 0.3 m (near-zero state). The experimental results suggested that HIP treatment at 1,220 C produced the best performance in microstructure transformation to the near-original state for the exposed blade of GTD-111 alloys as cast EQX. 2022, Microscopy Society of Malaysia. All rights reserved.